A Mobile Suitcase for Informatic Teachers Related to the “Digital” Didactic Goals of the 21st Century - Nothacker, Jens (Central European Journal of Educational Research, 2021)
This study deals with the optimal equipment of a mobile case for computer science teachers, which offers the possibility to teach the skills of the curricula from primary to high school of the 21st century. First, the Single Board Computers (SBCs) in question are filtered out from previous studies and the accessory parts required are determined through a quantitative market analysis. Then, by combining the results with a qualitative analysis according to Mayring, the degree of curricular coverage of individual accessories is determined and binarized. Afterwards, the optimal equipment of the mobile case is evaluated and established based on the cost overlap by horizontal summation and vertical inclusion of the necessary accessories after recording the prices and the budget. The results were clearly presented in network diagrams and lists. This study thus provides computer science teachers and computer science professors with a budget-dependent basis for making decisions about the contents of a mobile case for computer science lessons or a computer science laboratory for learning the skills of the curricula from primary to high school of the 21st century. The study closes with a summary and an outlook.